A Systematic Review of Treatments for Problematic Khat Use. (17th February 2020) - Ahmed, Sagal; Minami, Haruka; Rasmussen, Andrew
Abstract: Khat, a psychostimulant cultivated and commonly used in Eastern Africa and the Arabian penin-sula, has a longstanding history of use embedded within the cultures of these regions. Due to changing patterns of use and the adverse effects of dependence, khat has become a growing pub- lic health concern. Despite extensive findings regarding the detrimental psychiatric, physical, and social consequences of khat dependence, research on interventions in this area is glaringly sparse. The present paper aims to summarize the consequences of chronic khat use and review existing research on interventions.